ANALYSIS OF THE IMPACT OF ONLINE-BASED LEARNING MEDIA USING MICROSOFT TEAMS ON STUDENT'S UNDERSTANDING IN PHYSICS SUBJECT AT SMAN PAKUSARI - I Ketut Mahardika; Subiki Subiki; Detania Faridawati; Fungki Oktaviyati; Riki Gatti Kusuma (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2021)
The purpose of this study is to know the impact of online-based learning using Microsoft Teams on student’s understanding of Physics subjects. The research method uses a survey method with respondents collected from students of class X MIPA 5 of SMAN Pakusari. Samples were taken using random sampling techniques for up to 33 respondents from the students of class X MIPA 5 of SMAN Pakusari. The data analysis is conducted using the descriptive tables from the results of the questionnaire to determine the results of students' understanding of Physics subjects using MicroTeam-based based learning media. To determine the validity and reliability, the results of the questionnaire were tested using SPSS. The research result showed that among 33 respondents, 33% of students are indicated as having a good level of understanding and 67% of others had less level of understanding of Physics subjects using Microsoft Teams as learning media. Upon the students’ satisfaction level, it showed that 33% of students had a good level of satisfaction and 67% of others had less satisfaction level in learning Physics using Microsoft Teams. Also on the index of Microsoft Teams media influence, it showed that 30% of students are indicated as having a good influence level, and 70% of others had less influence level on learning Physics using Microsoft Teams. In the reliability test using SPSS, the Cronbach Alpha value was shown to be 0.73. It is concluded that online-based learning media using Microsoft Teams is less effective to be applied at SMAN Pakusari due to the poor results of its impact on student understanding, satisfaction and influence.